The Transition "School-University": Predictors of Academic Performance of First-year Students - Tatyana Saprykina (Высшее образование в России)
This study examines the educational achievements of first-year students. The aim is to evaluate the relationship between performance in pre-university period with the academic performance of first-year students through the lens of adaptation to the university environment. The theme of factors of academic achievement of students, on the one hand, is well developed in the American research tradition, where this issue is devoted to hundreds of works and dozens of different experimental plans. On the other hand, in Russia there are almost no studies which have examined this association on national representative samples and using longitudinal data. The presupposition of this study is the notion that educational outcomes of students, among other things, meaningful manner associated with characteristics of learning in high school. Studies that simultaneously link student achievement in school, and after – at the time the student, it is not enough. As predictors of student academic performance were selected characteristics of schools, student performance in school, and characteristics associated with additional education. The paper presents the results of correlation and regression analysis. The study revealed significant Pearson correlation coefficient between grades in grades 10-11 and grades at the University, however, none of the parameters did not exceed 0,3. As for the other predictors, it was found that academic performance at the university linked to school performance, the fact of studying in a selective school, participation in activities of career guidance, higher education on the humanitarian or socio-economic specialty.